Dynamic Mental Representations of Habitual Behaviours: Food Choice on a Web-Based Environment. - Gaspar, Rui; Palma-Oliveira, José Manuel; Corral-Verdugo, Victor (Psychology, Community & Health, 2016)
Aim: Rather than being rigid, habitual behaviours may be determined by dynamic mental representations that can adapt to context changes. This adaptive potential may result from particular conditions dependent on the interaction between two sources of mental constructs activation: perceived context applicability and cognitive accessibility. Method: Two web-shopping simulations offering the choice between habitually chosen and non-habitually chosen food products were presented to participants. This considered two choice contexts differing in the habitual behaviour perceived applicability (low vs. high) and a measure of habitual behaviour chronicity. Results: Study 1 demonstrated a perceived applicability effect, with more habitual (non-organic) than non-habitual (organic) food products chosen in a high perceived applicability (familiar) than in a low perceived applicability (new) context. The adaptive potential of habitual behaviour was evident in the habitual products choice consistency across three successive choices, despite the decrease in perceived applicability. Study 2 evidenced the adaptive potential in strong habitual behaviour participants - high chronic accessibility - who chose a habitual product (milk) more than a non-habitual product (orange juice), even when perceived applicability was reduced (new context). Conclusion: Results portray consumers as adaptive decision makers that can flexibly cope with changes in their (inner and outer) choice contexts.